IMAGE DATA SECURITY USING VERNAM CIPHER ALGORITHM - Supiyanto, Supiyanto; Werdhani, Anastasia Sri (Informatika, Universitas Jenderal Soedirman, 2024)
The Vernam Cipher algorithm is a symmetric key algorithm, as it uses the same key for encryption and decryption. It utilizes a binary number system with XOR operation to produce a series of bits. This study aims to implement the Vernam cipher algorithm to secure personal and confidential image data, which is at risk of misuse when shared through chat applications like Facebook, WhatsApp, and email. Therefore, developing image protection applications is crucial. The research explores whether the vernam cipher algorithm, working with single bits in block form and based on binary numbers, can effectively secure image data, specifically grey scale images with BMP and JPG extensions. The approach involves applying the Vernam cipher algorithm to programming language to create a data security application. The outcome is an image security application program, with test results indicating successful encryption with significant randomness. The decryption process with the Vernam cipher method can restore encrypted images to their original state, although some distortion may occur, especially with JPEG images. Decryption of BMP images is nearly flawless. The key for data security can vary in length and form, with encryption taking longer than decryption.